Wzorowe „niewiasty chrześcijańskie” w siedemnastowiecznym kazaniu okolicznościowym „Pszczółka w bursztynie” Franciszka Sitańskiego - Kaczor-Scheitler, Katarzyna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2014)
This article concerns the representation of two women: St. Dorothy, a martyr of Caeserea Mazaca, and Dorota Kątska, abbess of the Norbertines Order in the Zwierzyniec near Kraków, based on the sermon of the Bernadine Franciszek Sitański (ca. 1590–1643), entitled The Bee in Amber (Pszczółka w bursztynie, Kraków 1627). The author shall prove that in the sermon given on the nameday of the Norbetine abbess, the preacher largely focused on St. Dorothy. The portraits of the “Christian women” present the virtues of the heroines to commemorate their deeds, as well as encourage the sermon’s recipients to follow the example of these virtues.